Jakub Przyłuski (1512–1554): Outline of life and literary work against the background of the epoch (Lodz University Press, 2022)
The biography of Jakub Przyłuski is outlined in the volume. The characteristics of his poetry were associated with it. Against the background of the current state of research, selected elements of the writer’s and lawyer’s main work, Leges seu statuta ac privilegia Regni Poloniae, were presented. The research also covered the author’s activity as a town writer in Przemyśl, taking into account the background of the functioning of his office. Przyłuski’s correspondence with Stanisław Orzechowski was also discussed in the context of Piotr Kmita’s milieu, in whose circle he was a patron, and relations with the Reformation. Fragments of the Speech to the Polish Nobility by Orzechowski were also analyzed, serving as a kind of introduction to the work of Przyłuski, the Acts, statutes and privileges of the Kingdom of Poland. The volume also presents the history of the Benedictine monastery in Jeżów, which was presented as the cultural background of the childhood and youth of the later Przemyśl and Kraków writers.